2007
DOI: 10.1007/s00467-006-0298-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in children with chronic renal failure

Abstract: Psychiatric assessment was done according to the DSM-IV TR criteria in 19 children with predialysis chronic renal failure (CRF) and 19 children with end-stage renal disease on regular hemodialysis. The prevalence rate of psychiatric disorders in all the studied patients was 52.6%. Adjustment disorders were the most common disorders (18.4%), followed by depression (10.3%) and neurocognitive disorders (7.7%). Anxiety and elimination disorders were reported in 5.1 and 2.6%, respectively. The disorders were more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 24 publications
6
78
4
Order By: Relevance
“…There were statistically significant differences in the total QoL with the children in the control group. Our study rate of depression was higher than found by Bakr et al 19 in a study of 19 children with pre-dialysis chronic renal failure (CRF) and 19 children with end stage renal disease undergoing regular hemodialysis. The prevalence rate of psychiatric disorders in all the studied patients was 52.6%.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…There were statistically significant differences in the total QoL with the children in the control group. Our study rate of depression was higher than found by Bakr et al 19 in a study of 19 children with pre-dialysis chronic renal failure (CRF) and 19 children with end stage renal disease undergoing regular hemodialysis. The prevalence rate of psychiatric disorders in all the studied patients was 52.6%.…”
Section: Discussioncontrasting
confidence: 73%
“…The disorders were more prevalent in dialysis (68.4%) than in pre-dialysis patients (36.8%). 19 Similarly, in a study to assess depression, anxiety, and QoL in a cohort of children and adolescents with ESRD, were compared with healthy controls. Thirty-two children and adolescents 8-18 years of age were enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of depression in children and adolescents is not well understood compared to adults, however it is considered as a result of interaction between stressful events of chronic illness and associated problems such as family-related problems, economic difficulties, social factors as peer group or school achievement (Bould et al, 2013). A study made by Bakr et al (2007) reported that, psychiatric disorders in all the studied pediatric patients at El-Mansoura University Children's Hospital were adjustment disorders, neurocognitive disorders, anxiety, elimination disorders and depression. Another study (Hashad et al, 2015) represent 91.9% of children had depression that categorized into mild depression in 28.4% of children, more than one third of them had moderate depression and 24.3% of them had severe depression.…”
Section: Introductionmentioning
confidence: 99%
“…From them we could mention the lowering in levels of neurotropic factors deriving from the brain (BDNF) and low levels of serotine serumin patients with CKD. They also reveal uremia, which may be accompanied with irritation, trouble, sleeplessness and delayed development of secondary sexual features (Bakr et al, 2007;Fadrowski et al, 2006). Also Gerralda et al (1988) compared psychiatric elements of children waiting to receive dialyses and were receiving Hemodialyses with a control group.…”
Section: Emotional State and Psychiatric Changesmentioning
confidence: 99%